Prinsip Akuntabilitas, Transparansi Dan Value For Money Dalam Pengelolaan Keuangan Pada Masjid: (Studi Kasus Pada Masjid Baitul Gafur di Lingkungan Gebang) - Jannah, Siti Raodatul; Fitriyah, Nur; Lenap, Indria Puspitasari (Fakultas Ekonomi dan Bisnis Unram, 2025)
This study aims to determine the application of the principles of accountability, transparency and value for money in financial management at the Baitul Gafur Mosque. The research method used is a qualitative approach with descriptive analysis. Data collection techniques through observation, interviews and documentation. The informants of this study were the Mosque Takmir, Mosque Treasurer, Head of the Dakwah/Worship and Education Division of the Mosque and 3 Mosque Congregations. The results of the study indicate that accountability in the financial management of the Baitul Gafur Mosque has been running well, although financial records are still simple and not in accordance with the ISAK 35 guidelines. Transparency is attempted through openness of information, publication of financial reports verbally every Friday prayer and provision of clear information regarding income and expenditure of funds. However, there are still notes regarding the lack of detailed information regarding expenditure of funds. Value for money shows significant improvements in economics, from less economical in 2020 to very economical in 2022 and 2023. Efficiency in generating income tends to increase, and effectiveness in achieving income targets shows a dramatic increase in 2022 and 2023. The financial management of the Baitul Gafur Mosque is still carried out using a simple recording method, namely cash receipts and disbursements by the administrators because it is considered sufficient and does not confuse the administrators in categorizing each existing transaction.